You are on page 1of 6

SYSTEM THEORY

XIII

INTRODUCTION TO THE DISCRETE-TIME SYSTEMS ANALYSIS

1. Examples of Number Sequence z-Transforms

1.1. The Exponential Number Sequence


Definition: the exponential number sequence is given by the following expression:

{u[k ]} = e − a⋅k ⋅T , k ∈ N ,a ∈ R+ . (1.)

Proposition: given the exponential number sequence, with u[k ] = e − a⋅k ⋅T , a ∈ R+ , with the sampling
period T ., The z-transform of the exponential sampled data is given by the following expression:

[{[
Z e −a⋅k ⋅T ]}] = z − ez − a ⋅T . (2.)

Proof: U ( z ) can be written in power series form as:

U ( z ) = 1 + e − a⋅T ⋅ z −1 + e −2⋅a⋅T ⋅ z −2 + K =
(i) .
( ) (
= 1 + e − a⋅T ⋅ z −1 + e − a⋅T ⋅ z −1 + K )
2

Consider the following identity:

1
(ii) 1 + x + x2 + x3 + K = , x < 1.
1− x
Follows, from the notation (i).

z −1
U (z ) =
1
(iii) − a⋅T −1
= −1 − a ⋅T
; e − a⋅T ⋅ z −1 < 1 . 
1− e ⋅z z −e

1.2. The Unit-Step Number Sequence


Definition: the unit-step number sequence is given by the following expression:

0 k < 0
{u[k ]} =  . (3.)
1 k ≥ 0 , k ∈ N

Proposition: the z-transform of the unit-step number sequence is given by the following expression:

U (z ) =
z
. (4.)
z −1

Proof: from notation (2.) for a = 0 .

Definition: the unit-ramp number sequence is given by the following expression:

ST/DA/Rev2009 1
Introduction to Discrete-Time Systems Analysis

Fig. 1: The Exponential Data Sequence Fig. 2: The Unit-Step Data Sequence

0 k <0
{u[k ]} =  . (5.)
k k ≥ 0, k ∈ N

Proposition: given the sampling period T , the z-transform of the unit-ramp number sequence is given by
the following expression:

z ⋅T
U (z ) = .
(z − 1)2 (6.)

Proof: Consider the following relation in time-domain:

(i) lim
a →0 da
(
d − a⋅T
e )
= lim (− t ) ⋅ e − a⋅T = −t .
a →0

For the z-transform of the number sequence follows:

 d   −1
Z {[k ]} = lim  ⋅ (− 1) = (− 1) ⋅ lim z ⋅
z
⋅ T ⋅ e − a⋅T =
( )
(ii)
 a→0 da  z − e 
− a ⋅T 2

a →0
z − e − a⋅T

− z ⋅T z ⋅T
= (− 1) ⋅ =
(z − 1) (z − 1)2
2 

1.3. The Sine and Cosine Number Sequence

Proposition: given the sampling period T and the angular frequency ω , the z-transforms of the sine
and cosine number sequences are given by the following expressions:

z ⋅ sin ω ⋅ T
Z {sin[ω ⋅ k ⋅ T ]} = . (7.)
z − 2 ⋅ z ⋅ cos ω ⋅ T + 1
2

ST/DA/Rev2009 2
Theorems of the z-Transform

z ⋅ ( z − cos ω ⋅ T )
Z {cos[ω ⋅ k ⋅ T ]} = (8.)
z − 2 ⋅ z ⋅ cos ω ⋅ T + 1
2

Proof: with the Euler's theorem:

e j⋅ω⋅T − e − j⋅ω⋅T e j⋅ω⋅T + e − j⋅ω⋅T


(i) sin(ω ⋅ t ) = , cos (ω ⋅ t ) = .
2⋅ j 2

Follows, for the sine sampled data.

e j⋅ω⋅k ⋅T − e − j ⋅ω⋅k ⋅T 1 
sin[ω ⋅ k ⋅ t ] = Z {sin[ω ⋅ k ⋅ T ]} =
z
⋅ −
2⋅ j 2 ⋅ j  z − e j⋅ω⋅T
z 
− =
and (2.) z − e − j⋅ω⋅T 

z z − e − j⋅ω⋅T − z − e j⋅ω⋅T z ⋅ sin(ω ⋅ T )


= ⋅ 2 = 2
2⋅ j z − z ⋅ e
144244
(
j ⋅ω⋅T
+e − j ⋅ω⋅T
3
)
+ 1 z − 2 ⋅ z ⋅ cos(ω ⋅ T ) + 1 
= 2⋅cos (ω⋅T )

For the z-transform of the cosine number sequence the proof may be performed in the same manner.

2. Theorems of the z-Transform


Theorem (Addition and Subtraction): the z-transform of a sum of number sequences is equal to the
sum of the z-transforms of the number sequences.

[{ }]
Z u1 [k ] ± u 2 [k ] = U 1 ( z ) ± U 2 ( z ) . (9.)

Proof:

[{ } { }] ( )
∞ ∞ ∞
Z u1 [k ] ± u 2 [k ] = ∑ u1 [k ] ± u 2 [k ] ⋅ z − k =∑ u1 [k ]⋅ z − k ± ∑ u 2 [k ]⋅ z − k = 
k =0 k =0 k =0

[{ }]
= Z u1 [k ] ± Z u 2 [k ] [{ }]
Theorem (Multiplication by a Constant): the z-transform of a number sequence multiplied by a constant
is equal to the constant multiplied by the z-transform of the number sequence.

Z [{a ⋅ u[k ]}] = a ⋅ Z [{u[k ]}] = a ⋅U ( z ) . (10.)

Proof:

∞ ∞
Z [a ⋅ {u[k ]}] = ∑ a ⋅ u[k ]⋅ z − k =a ⋅ ∑ u[k ]⋅ z − k = a ⋅ U ( z ) 
k =0 k =0

Theorem (Real Translation): let n be a positive integer.

1. Z [{u[k − n]}] = z − n ⋅U ( z ) . (11.)

ST/DA/Rev2009 3
Introduction to Discrete-Time Systems Analysis

n −1
 
2. Z [{u[k + n ]}] = z ⋅ U (z ) − ∑ u[k ]⋅ z − k 
n
(12.)
 k =0 

Proof: 1.

Z [{u[k − n ]}] = u[− (n )] + u[− (n − 1)]⋅ z −1 + K + u[0 ]⋅ z − n + u[1]⋅ z − (n+1) + K =


14444 4244444 3
u [− ( n −i )]=0 for − ( n − i )<0

( )
= z − n ⋅ u[0 ]⋅ +u [1]⋅ z −1 + K = z − n ⋅ U ( z )
144424443 
=U ( z )

2.

Z [{u[k + n]}] = u[n]⋅ z 0 + u[n + 1]⋅ z −1 + u[n + 2]⋅ z −2 K =

(
= z n ⋅ u[0 ]⋅ z 0 + u[1]⋅ z −1 + K + u[n]⋅ z − n + u[n + 1]⋅ z −(n +1) + u[n + 2 ]⋅ z −(n + 2 ) + K

)
n −1
 
− u[0 ]⋅ z 0 − u[1]⋅ z −1 − K − u[n − 1]⋅ z −(n −1) = z n ⋅ U (z ) − ∑ u[k ]⋅ z −k  
 k =0 

Remark: comparison between formulas (11.) and (12.), and the real integration and real differentiation
and theorems of the Laplace transformation, respectively.

t  F (s )
L  ∫ f (t )dt  = Z [{u[k − n]}] = z − n ⋅U ( z )
0  s

 d n f (t ) 
 = s ⋅ F (s ) −
n
L  n −1

 dt n
 Z [{u[k + n ]}] = z ⋅ U (z ) − ∑ u[k ]⋅ z − k 
n

[
− s ⋅ f (0 ) + K + f (n −1) (0 )
n −1
]  k =0 

2.1. Multiplication of u[k ] by e a⋅k

Theorem (Complex Translation): the z-transform of the number sequence {e a ⋅k


}
⋅ u[k ] is

[{ }]
Z e a⋅k ⋅ u[k ] = U z ⋅ e − a . ( ) (13.)

Proof:

[{ }]
Z e a⋅k ⋅ u[k ] = u[0 ] + e a ⋅ u[1]⋅ z −1 + e 2⋅a ⋅ u[2]⋅ z − 2 + e 3⋅a ⋅ u[3]⋅ z −3 + K =

(
= u[0 ] + u[1]⋅ z ⋅ e − a )
−1
+ u[2]⋅ z ⋅ e − a( ) −2
(
+ u[3]⋅ z ⋅ e − a )
−3
+ K = U z ⋅ e −a( ) 

Remarks:

1. Compare the theorem (13.) and the equivalent theorem from the Laplace transformation, i.e.

[ ]
L e −α⋅t ⋅ f (t ) = F (s + α ) .

ST/DA/Rev2009 4
Theorems of the z-Transform

2. The z-transforms of the number sequences {e − a ⋅k


} { }
⋅ sin ω ⋅ k ⋅ T and e − a⋅k ⋅ cos ω ⋅ k ⋅ T are as follows.

z ⋅ e a ⋅ sin ω ⋅ T
[{
Z e − a⋅k ⋅ sin ω ⋅ k ⋅ T = }] z 2 ⋅ e 2⋅a − 2 ⋅ z ⋅ e a ⋅ cos ω ⋅ T + 1
.

Z e[{ − a ⋅k
]
⋅ sin ω ⋅ k ⋅ T } =
(
z ⋅ e a ⋅ z ⋅ e a − cos ω ⋅ T )
z 2 ⋅ e 2⋅a − 2 ⋅ z ⋅ e a ⋅ cos ω ⋅ T + 1

Theorem (The Initial Value): Given that the z-transform of the number sequence {u[k ]} is U (z ) . Then,
u[0 ] = lim U ( z ) . (14.)
z →∞

Proof:

U ( z ) = u[0 ] + u[1]⋅ z −1 + u[2]⋅ z −2 + u[3]⋅ z −3 + K = ;

For z → ∞ ⇒ u[0 ] .

Theorem (The Final Value): Given that the z-transform of the number sequence {u[k ]} is U (z ) . Then,
lim u[k ] = lim( z − 1) ⋅ U (z ) . (15.)
k →∞ z →1

Proof: consider the z-transform of the following number sequence.

n n

(i) Z [{u[k + 1]}− {u[k ]}] = lim ∑ u[k + 1]⋅ z − k − ∑ u[k ]⋅ z − k  =
n →∞
 k =0 k =0 

= lim [ − u[0 ] + = lim [ − u[0 ] +


n →∞ n →∞

+ u[1] − u[1]⋅ z −1 + ( )
+ 1 − z −1 ⋅ u[1] +

+ u[2]⋅ z −1 − u[2]⋅ z −2 + ( )
+ z −1 − z − 2 ⋅ u[2] +

+ u[3]⋅ z −2 − u[3]⋅ z −3 + ( )
+ z − 2 − z −3 ⋅ u[3] +

+K K+ +K K+

+ u[n]⋅ z − (n−1) − u[n]⋅ z − n + + (z −(n −1) − z −n )⋅ u[n] +

+ u[n + 1]⋅ z −n = ] + u[n + 1]⋅ z −n = ]


[( )(
= lim 1 − z −1 ⋅ u[1] + z −1 ⋅ u[2] + z − 2 ⋅ u[3] + K + z −(n −1) ⋅ u[n] + u[n + 1] ⋅ z − n − u[0 ]
n →∞
) ]
In notation (i) compute the following limit.

ST/DA/Rev2009 5
Introduction to Discrete-Time Systems Analysis

lim Z [{u[k + 1]}− {u[k ]}] = lim (u[n + 1] − u[0 ]) .


(i)
(ii)
z →1 n →∞

On the other hand, from the real translation theorem,

(iii) Z [{u[k + 1]}− {u[k ]}] = z ⋅ [U ( z ) − u[0 ]] − U ( z ) .

After pasting the notation (iii) into the notation (ii), follows,

lim( z − 1) ⋅ U ( z ) − 1 ⋅ u [0 ] = lim u[n + 1] − u[0 ] ⇒ lim u[n] = lim(z − 1) ⋅ U ( z ) 


z →1 n →∞ n →∞ z →1

Fig. 3: The Unit-Ramp Data Sequence

ST/DA/Rev2009 6

You might also like